Implementation tendencies and expert perspectives on physician-performed prehospital endotracheal intubation in Japan: Findings from the first round of a Delphi survey - Hiroaki Taniguchi; Kazuhiko Omori; Hiroki Nagasawa; Hiromichi Ohsaka; Youichi Yanagawa (PLoS ONE, 2026)
Standardization of prehospital endotracheal intubation (ETI) has been shown to be essential for improving first-pass success rates and minimizing complications. In Japan, however, physician-performed prehospital ETI lacks uniform implementation. To address this gap, we conducted a Delphi study to assess expert consensus on key practices and discrepancies between perceived appropriateness and actual use. We conducted the first round of a modified two-round Delphi study using a web-based questionnaire comprising 90 recommendation statements across eight domains, derived from the literature and a pilot study. Eligible participants were physicians with at least three years of prehospital emergency care experience and a minimum of 30 prehospital ETI cases. Statements were rated for perceived appropriateness and implementation on a 4-point Likert scale, with consensus defined as a positive response rate of ≥70.0%. Free-text comments were also collected to explore areas of discrepancy. Among 58 invited physicians, 40 (69.0%) responded, of whom 65.0% had more than 15 years of prehospital experience. Consensus on appropriateness was achieved for 72 of 90 items (80.0%), whereas consensus on implementation was reached for 57 items (63.3%). At the domain level, appropriateness consensus was highest in the Confirmation domain (100%; 9/9 items) and lowest in the Environment during endotracheal intubation domain (25%; 1/4 items). Discrepancies between perceived appropriateness and implementation were observed across multiple domains, including peripheral equipment and medication-related practices. At the item level, checklist use was considered appropriate by 65.0% of respondents but reported as implemented by only 10.0%. These findings highlight gaps between perceived appropriateness and implementation of physician-performed prehospital ETI practices in Japan, underscoring the need for context-sensitive, locally adapted protocols.